Facility planning and design - Bedi, Siddharth
"Facility planning is concerned with the design, layout, and accommodation of people, machines and activities of a system or enterprise within a physical spatial environment. Facility planning is very important in a manufacturing process due to their effect in achieving an efficient product flow. For an organization to have an effective and efficient manufacturing unit, it is important that special attention is given to facility layout. Facility layout is an arrangement of different aspects of manufacturing in an appropriate manner as to achieve desired production results. Facility layout considers available space, final product, safety of users and facility and convenience of operations. The informal organization is the network, unrelated to the firm's formal authority structure, of social interactions among its employees. It is the personal and social relationships that arise spontaneously as people associate with one another in the work environment. The supervisor must realize that the informal organization affects the formal organization. The informal organization can pressure group members to conform to the expectations of the informal group that conflict with those of the organization. A model facility layout should be able to provide an ideal relationship between raw material equipment, manpower and final product at minimal cost under safe and comfortable environment. The book is designed to help the students and professionals to quickly acquire the knowledge and skills they need for this subject."